Safe Spaces and Critical Places: Youth Programming and Community Support (LEARNing Landscapes, 2024)
In this article we explore the work of two after-school programs in Toronto, Ontario. Our Youth Success (OYS) is a community-based mentoring program dedicated to lowering the push-out rates of students of Spanish and/or Portuguese-speaking descent. In the Youth Speak Program (YSP), community activists use spoken word poetry and rapping as a vehicle for Black students to express their emotional lives. The data we present come from two separate studies which both used ethnographic approaches, focusing on observation and interviews with participants (Hammersley & Atkinson, 2019). Using Critical Race Theory (CRT), we examine interview data on how the pedagogical relationships developed in these spaces promote the wellbeing of Latinx and Black youth beyond academic outcomes. We argue that these spaces provide insight into the transformative possibilities of critical pedagogies for the wellbeing and healing of communities who have long been marginalized from mainstream institutions.
Keywords: youth; race; education; marginalization; transformation; equity